The European Medicines Agency approval of axitinib (Inlyta) for the treatment of advanced renal cell carcinoma after failure of prior treatment with sunitinib or a cytokine: summary of the scientific assessment of the Committee for Medicinal Products for Human Use - Tzogani, Kyriaki; Mickisch, Gerald (The oncologist, 2015)
Axitinib is a tyrosine kinase inhibitor of vascular endothelial growth factor receptor 1 (VEGFR-1), VEGFR-2, and VEGFR-3. Based on the positive opinion from the European Medicines Agency (EMA), a marketing authorization valid throughout the European Union (EU) was issued for the treatment of advanced renal cell carcinoma (RCC) after failure of prior treatment with sunitinib or a cytokine. The demonstration of clinical benefit for axitinib was based on a phase III, randomized, open-label, multicenter study of axitinib compared with sorafenib in patients with advanced RCC after failure of a prior systemic first-line regimen containing one or more of the following agents: sunitinib, bevacizumab plus interferon-α, temsirolimus, or cytokines. In the primary analysis, a 2-month increase in median progression-free survival (PFS) was observed for axitinib compared with sorafenib (hazard ratio [HR]: 0.665; 95% confidence interval [CI]: 0.544-0.812; p < .0001). In the subgroup of patients with a prior cytokine-containing regimen, the increase in median PFS associated with axitinib was 5.4 months (updated analysis, HR: 0.519; 95% CI: 0.375-0.720; p < .0001). In the subgroup of patients with prior sunitinib treatment, the increase in median PFS was 1.4 months (updated analysis, HR: 0.736; 95% CI: 0.578-0.937; p = .0063). The analysis of overall survival showed no statistically significant survival benefit of axitinib over sorafenib in patients previously treated with cytokine-containing regimens (HR: 0.813; 95% CI: 0.556-1.191) or sunitinib (HR: 0.997; 95% CI: 0.782-1.270). The most common treatment-related adverse events associated with axitinib included diarrhea, hypertension, fatigue, nausea, decreased appetite, dysphonia, and palmar-plantar erythrodysesthesia. Most of these events were mild or moderate in severity. This paper summarizes the scientific review of the application leading to approval in the EU. The detailed scientific assessment report and product information, including the summary of product characteristics, are available on the EMA website (http://www.ema.europa.eu).